Recurrent fetal syndromic spina bifida associated with 3q26.1-qter duplication and 5p13.33-pter deletion due to familial balanced rearrangement - Egle Preiksaitiene; Eglė Benušienė; Zivile Ciuladaite; Vytautas Šliužas; Violeta Mikštienė; Vaidutis Kučinskas (Elsevier, 2016)
Objective: Neural tube defects belong to the second most common group of congenital anomalies, after heart defects, which can be diagnosed by prenatal ultrasonography. Rarely, neural tube defects can be associated with chromosomal abnormalities, including full and partial aneuploidies. We report a familial fetal case with syndromic spina bifida and discuss its association with partial 3q duplication and partial 5p deletion. Materials and methods: Clinical findings of three affected family members in two generations and two carriers of the balanced translocation are described. Conventional cytogenetic and fluorescence in situ hybridization (FISH) analysis of the carrier, as well as subtelomeric multiplex ligation-dependent probe amplification (MLPA) and array comparative genomic hybridization (CGH) analysis on the DNA extracted from affected family members was performed. Results: Subtelomeric FISH analysis of the proposita revealed balanced reciprocal translocation between the long arm of chromosome 3 and short arm of chromosome 5. Subtelomeric MLPA screening of the first child revealed the deletion in 5p15.33 and duplication in 3q29 chromosomal loci, the finding consisting of the unbalanced rearrangement involving the short arm of chromosome 5 and long arm of chromosome 3. Array CGH analysis of the DNA of the second affected child revealed a 31.1Mb duplication of 3q26.1-qter and a 33.6Mb deletion of 5p13.33-pter. Conclusion: Our report serves to emphasize the consistency in the prenatal sonographic feature of spina bifida in consecutive pregnancies with fetuses associated with partial trisomy 3q (3q26.1-qter) and partial monosomy 5p (5p13.33-pter). The use of molecular cytogenetic technologies such as array CGH and FISH is important for clarifying any type of unbalanced chromosome rearrangement.